Physiotherapy Students Willingness To Report Misconduct To Protect The Patient’s Interests In Chennai - Malarvizhi1 , Bhagya Lakshmi K2 , Hariharan S3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Backgroung: Applying the ethics in practice is more essential than just learning it. Any sought of misconductto the patient is not just an ethical issue but it will also degrade the professionalism and it brings a sense ofinsecurity in patients and this will slow down the progress of treatment. So it is not only important to avoidthe ethical issues and misconduct but it is also necessary to stand against ethical issues that happen within theorganization that may done by colleagues or higher authorities without any dilemma. Objective: This studyaims to find out the difficulties and dilemmas of the physiotherapist in ethical decision making and disclosingthe misconduct of their colleagues without any hesitation. Methodology: A close ended questionnaire wasused to assess the willingness of the student physiotherapist to expose the misconduct which might bean internal or external disclosure. The questionnaire consisted of two clinical scenarios which were mostlikely to arise in a work place. Each scenario consisted of 5 questions that rated the severity, likelihood ofconfronting, internal disclosure, external disclosure to the association and external disclosure to media. Thescoring was based on five point likert scale. It was a study that was done with convenient sampling method.The questionnaire was given to 100 Physiotherapy students in Chennai of both the sexes who were willingto participate in the study. Result: From the statistical analysis, there is a significant difference obtained forthe likelihood of reporting the manager’s misconduct than colleague’s misconduct. Also their willingnessto report internally within the organization is greater than that of reporting externally to the associationand to the media. Conclusion: Ethics being a part of Physiotherapy curriculum, these students have wellunderstood the ethical and professional behavior and have good ethical acceptance. Hence we conclude thatthe students do understand the seriousness of any misconduct of a therapist to the patient and are willing toexpose any misconduct they encounter to the internal or external environment.